Air versus oxygen in ST-segment-elevation myocardial infarction - Stub, D.; Smith, K.; Bernard, S.; Nehme, Z.; Stephenson, M.; Bray, Janet; Cameron, P.; Barger, B.; Ellims, A.; Taylor, A.; Meredith, I.; Kaye, D. (2015)
Background: Oxygen is commonly administered to patients with ST-elevation-myocardial infarction despite previous studies suggesting a possible increase in myocardial injury as a result of coronary vasoconstriction and heightened oxidative stress. Methods and Results: We conducted a multicenter, prospective, randomized, controlled trial comparing oxygen (8 L/min) with no supplemental oxygen in patients with ST-elevation-myocardial infarction diagnosed on paramedic 12-lead ECG. Of 638 patients randomized, 441 patients had confirmed ST-elevation-myocardial infarction and underwent primary endpoint analysis. The primary end point was myocardial infarct size as assessed by cardiac enzymes, troponin I, and creatine kinase. Secondary end points included recurrent myocardial infarction, cardiac arrhythmia, and myocardial infarct size assessed by cardiac magnetic resonance imaging at 6 months. Mean peak troponin was similar in the oxygen and no oxygen groups (57.4 versus 48.0 µg/L; ratio, 1.20; 95% confidence interval, 0.92-1.56; P=0.18). There was a significant increase in mean peak creatine kinase in the oxygen group compared with the no oxygen group (1948 versus 1543 U/L; means ratio, 1.27; 95% confidence interval, 1.04-1.52; P=0.01). There was an increase in the rate of recurrent myocardial infarction in the oxygen group compared with the no oxygen group (5.5% versus 0.9%; P=0.006) and an increase in frequency of cardiac arrhythmia (40.4% versus 31.4%; P=0.05). At 6 months, the oxygen group had an increase in myocardial infarct size on cardiac magnetic resonance (n=139; 20.3 versus 13.1 g; P=0.04). Conclusion: Supplemental oxygen therapy in patients with ST-elevation-myocardial infarction but without hypoxia may increase early myocardial injury and was associated with larger myocardial infarct size assessed at 6 months.